Study of the corrosion behavior of cast Ti2AlNb alloy in HF–HNO3 solution - Yunyun Liu; Xianfei Ding; Lihong Wu; Xin Feng; Jiabin Zuo; Yunan Zhang; Lei Wen (Journal of Materials Research and Technology)
Based on immersion weight loss and electrochemical methods, the corrosion behavior of cast Ti2AlNb alloy in HF–HNO3 solution was investigated. The corrosion effects of HF and HNO3 on Ti2AlNb alloy were elucidated by examining the impact of varying concentrations of HF and HNO3 in mixed pickling solution on corrosion rate and surface roughness, as well as comparing and analyzing changes in macroscopic surfaces, microscopic morphology, and three-dimensional morphology before and after pickling. The electrochemical behavior of Ti2AlNb alloys in different concentrations of HF and HNO3 solutions was revealed by measuring the OCP-time and polarization curves of Ti2AlNb alloys in HF–HNO3 mixed pickling solutions. The experimental results indicated that the corrosion rate of Ti2AlNb alloy increased linearly with the increasing concentrations of HF and HNO3. Surface roughness increases with higher HF content, but decreases with higher HNO3 content after reaching a certain maximum value. The high concentrations of HNO₃ exert a pronounced passivation effect, which results in a reduction of surface roughness. However, it also has the tendency to produce pitting corrosion in coarse O/α2 phases at grain boundaries and within the grain. Scanning Kelvin probe atomic force microscopy (SKPFM) combined with microstructural analysis revealed that the electrochemical system consisting of matrix B2 phase and secondary phase governs the high localized dissolution rate of Ti2AlNb alloy. Additionally, the segregation of elements at grain boundaries accelerates corrosion, leading to more severe degradation in those regions. This study provides an experimental basis for understanding the corrosion behavior of Ti2AlNb alloy in HF–HNO3 solution.